INDONESIAN EFL STUDENTS’ PERCEPTION ON HELLO TALK APPLICATION IN FOSTERING SPEAKING - Damayanti, Alfinah; Hifdil, Muhammad; Beny Hamdani, Islam (Universitas islam Negeri Alauddin Makassar, 2024)
This study aims to investigate how students perceive the implementation of Communicative Language Teaching, specifically utilizing the HELLOTALK APP, to enhance their speaking skills. University of Islamic Zainul Hasan Genggong students participated in this descriptive qualitative research, which involved data collection through observation, field notes, and interviews. The analysis employed methods such as data reduction, data display, and conclusion. The findings indicated that most students recognized the positive impact of HELLOTALK APP in classroom activities, attributing it to the development of language skills and increased self-confidence. Although they found its implementation somewhat challenging, students expressed a preference for code-switching by the teacher during classroom activities. They also favored active discussion in pairs or groups, focusing on their respective fields of study, and recommended the integration of additional tools like online platforms and applications to enhance the learning process.